Optimization of the system of secondary ambulatory care institutions through the introduction of public-private partnership mechanisms - V. V. Kravchenko (Kazimierz Wielki University, 2017)
Introduction. The current problem of the domestic health care system is to increase the availability and effectiveness of medical care provided in communal consultative-diagnostic centers (KCTS). The purpose of the research: to substantiate expediency of optimization of the system of communal consulting and diagnostic centers on the basis of the introduction of mechanisms of public-private partnership (PPP). Materials and methods. The research is carried out using the method of system approach and analysis. The information base for its realization was the scientific work of specialists in the organization and management of health care, regulatory documents on the problem, as well as the results of their own research. Research results. The results of the comprehensive medical and social analysis of the state of the organization of medical care in the existing communal KDCs, obtained on the basis of official statistical reporting, sociological surveys of patients and doctors of KCC, experts' assessments and SWOT analysis, showed unsatisfactory financing and material and technical equipment of the KCC, inconsistency of quality of medical care in the KDC, the modern needs of the population, the inability of the current model of KDC to provide medical, social and economic efficiency, which necessitates the search the ways of development and improvement of activity of consulting and diagnostic centers. System analysis of domestic and foreign literature has shown that the prospect of the development of municipal KDCs is the formation of their new organizational model with the economic mechanism on the principles of PPP. In order to move the system to the principles of PPP in Ukraine there is an institutional base, which is represented by two laws. The article shows the directions of PPP development in health care and the prospects and advantages of its implementation. Defined external and internal conditions for the development of PPP, practical measures are needed to implement PPP in the system of consulting and diagnostic service. Conclusions The prospect of development of consulting and diagnostic assistance is the formation of its new organizational model with the economic mechanism on the principles of PPP.